2019
DOI: 10.1108/nbri-07-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Lady first? The gender difference in the influence of service quality on online consumer behavior

Abstract: Purpose This paper aims to articulate the gender differences in the influence of service quality on online consumer behavior. Design/methodology/approach Through data collected via a Web-based questionnaire survey from 330 consumers in China, this study builds and analyzes a structural equation model, using five dimensions of E-service quality, customer satisfaction and customer loyalty, and focuses on the moderation test of gender. Findings This study finds that first, efficiency dimension of e-service qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 86 publications
(101 reference statements)
5
29
1
8
Order By: Relevance
“…Positive perceptions of an online retailer's post-sale services may enhance consumers' online shopping experiences, which in turn shapes their satisfaction with a retailer. This is consistent with prior research by Martín and Jimenez (2011); Rita et al (2019), and Wang and Kim (2019), who revealed that service quality has a direct influence on customer satisfaction.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Positive perceptions of an online retailer's post-sale services may enhance consumers' online shopping experiences, which in turn shapes their satisfaction with a retailer. This is consistent with prior research by Martín and Jimenez (2011); Rita et al (2019), and Wang and Kim (2019), who revealed that service quality has a direct influence on customer satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…In the view of Morgan and Hunt (1994) , the act of maintaining and establishing relational exchanges represents a key change in marketing practice and theory, further stating that their theory applies to all relational exchanges connecting consumers and suppliers. Prior studies ( Crosby et al, 1990 ; Morgan and Hunt, 1994 ; Wang and Kim, 2019 ) have conceptualized the effect of relationship marketing on consequences as completely mediated by one or both of the interpersonal constructs of satisfaction and trust. Research also points to satisfaction and trust as key determinants of long-term relationships in an online environment and customer repurchase intention ( Agag and El-Masry, 2016 ; Al-Adwan and Al-Horani, 2019 ; Rita et al, 2019 ).…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of customer satisfaction on customer loyalty is more substantial for females than males (Wang and Kim 2019). Service quality is, however, important to both male and female customers.…”
Section: Content Analysis Of Findingsmentioning
confidence: 99%